The Impact of My.Bi Educational Video on Early Breastfeeding Initiation (IMD) Implementation: A Quasi-Experimental Study - Yenteo, Pipin; Ahmad, Mardiana; Idrus, Hasta Handayani; Darmawansyah, Darmawansyah; Nontji, Werna (Journal of Neonatal Surgery, 2025)
Background: IMD is the beginning of successful breastfeeding, can prevent or reduce infant mortality and is also believed to help increase the body's resistance to risky diseases. IMD as a major proportion of breastfeeding within the first hour after birth influences mothers to breastfeed optimally. Early breastfeeding initiation has an important influence on the success of mothers in providing breast milk so that this needs to be prepared since pregnancy, the preparation that can be done is by providing education as the first step of a health promotion approach in third trimester pregnant women. Objective: to analyse the effect of using My.Bi educational video on the implementation of IMD. Methods: Research and Development for My.Bi video development and quantitative research using Quasi Experiment, One Group Pretest-Postest Design approach. My.Bi educational video through FGD stages, designing videos, developing and validating My.Bi educational video learning media with stages; media needs analysis, learning media development design, expert test validation, TAM test and final media product. Data analysis of IMD implementation using the Chisquare test. Results: showed that the media developed in the form of My.Bi animated videos were suitable for use. The results of the analysis show that there is a significant effect on the implementation of IMD with a significance value of 0.000 <0.05 so it can be concluded that providing education using My.Bi educational media affects the implementation of IMD